INCLUSION OF AN INTELLECTUAL DISABILITY STUDENT IN PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2020)
Neurodevelopmental Disorders is a set of changes that has its onset in the child's developmental period. One of the manifestations of this disorder is Intellectual Disability, which occurs during the child's development, causing motor, speech and social failures. The stimuli are extremely important to have an evolution in the cognitive, motor, affective and social development, besides promoting inclusion. Objective of this study was to identify the effectiveness of motor stimulation in a student with intellectual disabilities in physical education classes. The present study is a case report that developed in a 15 years old with intellectual disability Intellectual Development Disorder. The Francisco Rosa Neto Motor Development Scale was used as an assessment instrument. The tests were applied in 50-minute sections to apply all the tests in the manual, namely fine motor skills, overall motor skills, balance, body scheme, organization. spatial, temporal organization and laterality. After initial evaluation, two further evaluations were performed during the 10-week stimulation period, one on the 5th and the 10th week. Having some evolutions in certain abilities such as fine motor coordination, balance, body schema, temporal organization, being verified statistically significant improvement already in the 5th week of stimulation, the spatial organization showed statistically significant improvement in the 10th week and the body schema skills, temporal organization presented statistically significant improvement on week 5 and 10, indicating that there was a statistically significant improvement in both periods evaluated. In the evaluation of laterality, it was found that the individual is complete right-handed. It is concluded that motor stimulation acts positively on the motor skills of children with intellectual disabilities.
Keywords: Intellectual Disability; Physical Education; Motor Development Scale; Inclusion